Pengaruh ROA, ROE, NPM, Dan EPS Terhadap Harga Saham Pada Perusahaan Makanan Dan Minuman Yang Tercatat Pada Bursa Efek Indonesia Tahun 2019-2021 - Muhammad Habibulloh; Nur Suci I. Mei Murni (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the effect of roa, roe, npm, and eps on stock prices in food and beverage companies listed on the Indonesia Stock Exchange in 2019-2021. This study uses quantitative research methods. For the data to be studied using the purpose sampling technique with the data source used is secondary data. The population used in this study is a food and beverage sub-sector company listed on the Indonesia Stock Exchange in the period 2019 to 2021. The results of this study are 1) ROA has no effect on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2019-2021. 2) ROE has no effect on stock prices in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2021. 3) NPM has no effect on stock prices in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2021. 4) EPS has no effect on stock prices in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2021.